The epstein-Barr virus and the pathogenesis of lymphoma - Vockerodt, M.; Yap, L.F.; Shannon-Lowe, C.; Curley, H.; Wei, W.B.; Vrzalikova, K.; Murray, P.G. (John Wiley & Sons, 2015)
Since the discovery in 1964 of the Epstein-Barr virus (EBV) in African Burkitt lymphoma, this virus has been associated with a remarkably diverse range of cancer types. Because EBV persists in the B cells of the asymptomatic host, it can easily be envisaged how it contributes to the development of B-cell lymphomas. However, EBV is also found in other cancers, including T-cell/natural killer cell lymphomas and several epithelial malignancies. Explaining the aetiological role of EBV is challenging, partly because the virus probably contributes differently to each tumour and partly because the available disease models cannot adequately recapitulate the subtle variations in the virus-host balance that exist between the different EBV-associated cancers. A further challenge is to identify the co-factors involved; because most persistently infected individuals will never develop an EBV-associated cancer, the virus cannot be working alone. This article will review what is known about the contribution of EBV to lymphoma development. Copyright (c) 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.